The Moderating Effect of Family Ownership on Earnings Management and Stock Price Crash Risk - Sakti, Aswin Parmita; Lubis, Arief Wibisono (Universitas Prasetiya Mulya, 2025)
This study examines the influence of earnings management on stock price crash risk within publicly listed companies in Indonesia. Additionally, it explores the moderating role of family ownership in this relationship, assessing whether it strengthens or weakens the connection between earnings management and stock price crash risk. The research employs an unbalanced panel data regression framework, utilizing dynamic panel data estimation through the system-GMM approach. Empirical findings indicate that accrual-based earnings management significantly increases the likelihood of stock price collapse, whereas real earnings management exerts only a marginal positive effect on crash risk. Furthermore, results suggest that family ownership amplifies the impact of earnings management on stock price crash risk, implying that firms with family ownership engage in more aggressive earnings manipulation practices, which in turn heighten the probability of future stock price crashes.